Physicochemical characteristics and finite element simulation of firmness in soursop fruits (annona muricata l. cv. elita) during postharvest (2012)
Soursop fruits (Annona muricata L. cv. Elita) at different ripening stages were evaluated for their physico-chemical characteristics: total soluble solids (TSS), acidity and pH. Firmness was determined through application of puncture textural tests. The modeling and simulation of this parameter was carried out on Autodesk Inventor Professional 11.0 (ANSYS® Technology). The fruits showed an upward trend regarding TSS and acidity, reaching maximum values of 12.8 °Brix, 0.74% acidity and pH below 3.43, all of which coincide with consumption maturity as observed on day 6. Firmness showed a decreasing trend throughout the entire postharvest period, with values of 79.43 N for day 0 and 3.62 N for day 9. Finite element modeling and simulation of firmness and its correlation with experimental data allowed calculating the fracture force of the fruits with an exactness of more than 90%. As it prevents physically altering the product, this application becomes an nondestructive alternative for firmness assessment, useful in storage, transport, fresh consumption, packaging and processing.